The Discursive Construction of Foreign Language Pedagogy at the University Level in Poland against the Background of the European Qualifications Framework - Nosidlak, Katarzyna (Księgarnia Akademicka Publishing, 2021)
Katarzyna Nosidlak’s book focuses on the theory and practice of foreign language pedagogy construed on a national scale for the needs of higher education systems in Poland under the pressures of international requirements. It raises contemporary issues of official educational discourses on language policy in Europe, which are significant for shaping the vision of the world shared by humans in interindividual communication in general and English as a second language in particular. Approaching the European Qualifications Framework and the Polish Qualifications Framework as tools for coordinating and comparing the content and results of education in the EU Member States at all levels, from basic to post-secondary, the book essentially enriches the knowledge of foreign language teaching and learning in the era of unification of laws on education. The notable achievements of Katarzyna Nosidlak’s book lie in its emphasis on the role of discourses and discursive practices in social life, including the formation of the Polish education system on the example of language pedagogy, its revelation of the consequences of the application of the perspective of social constructivism for communicative practices in foreign language teaching, and its provision of a comprehensive overview of legal acts and publications on the qualifications framework for lifelong learning.